ABT-737 Triggers Caspase-Dependent Inhibition of Platelet Procoagulant Extracellular Vesicle Release during Apoptosis and Secondary Necrosis In Vitro - Wei, Hao; Harper, Matthew T. (Thrombosis and Haemostasis, 2019)
Platelet lifespan is limited by activation of intrinsic apoptosis. Apoptotic platelets are rapidly cleared from the circulation in vivo. ABT-737 triggers platelet apoptosis and is a useful tool for studying this process. However, in vitro experiments lack clearance mechanisms for apoptotic platelets. To determine whether apoptotic platelets progress to secondary necrosis, apoptosis was triggered in human platelets with ABT-737, a BH3 mimetic. Platelet annexin V (AnV) binding, release of AnV+ extracellular vesicles (EVs), and loss of plasma membrane integrity were monitored by flow cytometry. ABT-737 triggered AnV binding, indicating phosphatidylserine exposure, release of AnV+ EVs, and a slow loss of plasma membrane integrity. The latter suggests that apoptotic platelets progress to secondary necrosis in vitro. These responses were dependent on caspase activation and Ca2+ entry. Surprisingly, although intracellular Ca2+ concentration increased, AnV+ EV release was not dependent on the Ca2+-dependent protease, calpain. On the contrary, ABT-737 downregulated the ability of the Ca2+ ionophore, A23187, to trigger calpain-dependent release of AnV+ EVs. This was dependent on caspase activity as, when caspases were inhibited, ABT-737 increased the ability of A23187 to trigger AnV+ EV release. These data suggest that apoptotic platelets progress to secondary necrosis unless they are cleared. This may affect the interpretation of ABT-737-triggered signaling in platelets in vitro. Ca2+-dependent AnV+ EV release is downregulated during apoptosis in a caspase-dependent manner, which may limit the potential consequences of secondary necrotic platelets.
Keywords: platelets; apoptosis; microparticles; extracellular vesicles; caspase